Preparation method and application of modified halloysite nanotube reinforced MTES / VTMS-based SiO2 aerogel

By combining modified Elosite nanotubes with MTES/VTMS-based SiO2 aerogels, low shrinkage and excellent adsorption performance were prepared, which solved the problem of high shrinkage of existing silica aerogels and achieved application in the fields of building energy conservation, thermal insulation and oil spill adsorption.

CN119633758APending Publication Date: 2025-03-18HENAN POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411790762.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing silica aerogel has a high shrinkage rate and complex preparation process, which limits its application range.

Method used

By combining the elolite nanotubes with MTES/VTMS-based SiO2 aerogel, the preparation method of the modified elolite nanotube enhanced MTES/VTMS-based SiO2 aerogel, including hydrolysis and condensation reaction, solid-liquid separation, washing and drying, aerogels with low shrinkage and excellent adsorption properties were prepared.

Benefits of technology

The modified Elosite nanotube enhanced MTES/VTMS-based SiO2 aerogel has achieved low shrinkage, hydrophobicity and adsorption, good thermal stability and low thermal conductivity, and is suitable for building energy conservation, thermal insulation and oil spill adsorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633758A_ABST
    Figure CN119633758A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of modified halloysite nanotube reinforced MTES / VTMS (Methylene Tetramethylthionyl Sulfonate / Vapor Transistor Mass Spectrometry)-based SiO2 aerogel. The preparation method comprises the following steps: (1) mixing halloysite nanotubes, octadecyl trimethoxysilane, tetraethoxysilane, absolute ethyl alcohol and ammonia water, and carrying out hydrolytic condensation reaction to prepare modified halloysite nanotubes; (2) fully stirring methyltriethoxysilane, vinyltrimethoxysilane, deionized water and absolute ethyl alcohol, and then adding hydrochloric acid to adjust the pH value for hydrolysis to obtain a precursor solution; (3) mixing the modified halloysite nanotube with the precursor solution to obtain a mixed solution; and (4) adding ammonia water into the mixed solution to adjust the pH value, standing at normal temperature, aging and drying. The modified halloysite nanotube reinforced MTES / VTMS-based SiO2 aerogel disclosed by the invention is relatively low in shrinkage rate, has certain hydrophobicity and adsorbability, and is good in thermal stability and low in thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aerogel materials, and specifically relates to a modified halloysite nanotube-enhanced MTES / VTMS-based SiO 2 Preparation method of aerogel and its application. Background Art

[0002] The construction industry is one of the largest sources of energy consumption in the world, and most of this building energy consumption is used to maintain a suitable temperature in the building. Studies have shown that proper insulation can reduce nearly 70% of the energy loss in the construction industry. Therefore, the development of building insulation materials can effectively reduce the energy demand of buildings and alleviate the environmental pollution caused by energy consumption. Traditional building insulation materials such as rigid polyurethane foam (RPF) and expanded polystyrene (EPS), which are derived from petroleum, may cause environmental degradation due to their non-biodegradable properties. In addition, the high organic content makes the foam thermally unstable and produces a large amount of heat and toxic gases when burned, which not only causes air pollution but also endangers people's health. Low-cost insulation materials such as mineral wool and expanded perlite, their production process is related to excessive carbon emissions and requires high temperature conditions, which is not conducive to the sustainable development of the environment. Therefore, it is necessary to seek a new type of insulation material. Silica aerogel is a nanomaterial with a three-dimensional network skeleton structure. Due to its low density, high porosity, low thermal conductivity and other characteristics, it is considered to be an ideal insulation material. However, pure silica aerogel also has problems such as low mechanical strength, large shrinkage, and complex preparation process, which to some extent limits its application scope.

[0003] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention

[0004] The object of the present invention is to provide a modified halloysite nanotube-enhanced MTES / VTMS-based SiO 2 The invention discloses a method for preparing aerogel and application thereof, which are helpful to solve or improve the problem of high shrinkage rate of pure silica aerogel in the prior art.

[0005] In order to achieve the above object, the present invention provides the following technical solution: a modified halloysite nanotube enhanced MTES / VTMS based SiO 2The preparation method of aerogel comprises the following steps: (1) mixing halloysite nanotubes, octadecyl trimethoxysilane, tetraethyl orthosilicate, anhydrous ethanol and ammonia water for hydrolysis and condensation reaction to obtain a white suspension, performing solid-liquid separation on the white suspension, collecting the obtained solid, washing and drying the solid to obtain modified halloysite nanotubes; (2) fully stirring methyl triethoxysilane, vinyl trimethoxysilane, deionized water and anhydrous ethanol, adding hydrochloric acid to adjust the pH value for hydrolysis to obtain a precursor solution; (3) mixing the modified halloysite nanotubes and the precursor solution to obtain a mixed solution; (4) adding ammonia water to the mixed solution to adjust the pH value, mixing evenly, standing at room temperature to obtain a wet gel, aging and drying to obtain the modified halloysite nanotube enhanced MTES / VTMS-based SiO 2 Aerogel.

[0006] Preferably, in step (1), the mass ratio of halloysite nanotubes to octadecyltrimethoxysilane is greater than 1, the mass ratio of octadecyltrimethoxysilane to tetraethyl orthosilicate is 0.1-10; the mass ratio of halloysite nanotubes, anhydrous ethanol and aqueous ammonia is 1:(25-30):(5-10).

[0007] Preferably, in step (1), the temperature of the hydrolysis condensation reaction is 50-65° C., and the reaction time is 1-2 h; thereafter, the reaction is continued under stirring at room temperature for 12-24 h to obtain a white suspension.

[0008] Preferably, in step (1), the solid-liquid separation of the white suspension is achieved by centrifugation, the centrifugal speed is 5000-7000 rpm, and the centrifugal time is 5-10 min.

[0009] Preferably, in step (2), the molar ratio of methyltriethoxysilane to vinyltrimethoxysilane is (0.7-1):(0.1~1), and the molar ratio of methyltriethoxysilane, anhydrous ethanol and deionized water is 1:(5~9):(10~20); in step (3), the amount of the modified halloysite nanotubes is 1%-9% of the total mass of the methyltriethoxysilane and vinyltrimethoxysilane.

[0010] Preferably, in step (2), the acid is added to adjust the pH to pH=4-7; in step (2), the hydrolysis temperature is 25-60° C., and the hydrolysis time is 8-12 h.

[0011] Preferably, in step (3), the ammonia water is added to adjust the pH to pH=7-9; the mixing in step (3) refers to stirring first and then ultrasonic treatment, the frequency of the ultrasound is 20-60 Hz, and the time of the ultrasound is 0.5-2h.

[0012] Preferably, in step (4), the aging time is 12 to 48 hours; the drying temperature is 50 to 70° C., and the drying time is 24 to 72 hours.

[0013] The present invention also provides a modified halloysite nanotube-enhanced MTES / VTMS-based SiO 2 Aerogel, which adopts the following technical scheme: a modified halloysite nanotube reinforced MTES / VTMS-based SiO 2 Aerogel, the modified halloysite nanotube reinforced MTES / VTMS based SiO 2 The aerogel was prepared by the method described above.

[0014] The present invention also provides the modified halloysite nanotube-enhanced MTES / VTMS-based SiO 2 The application of aerogel adopts the following technical scheme: the modified halloysite nanotubes as described above strengthen the MTES / VTMS-based SiO 2 The application of aerogel in at least one of building energy saving, thermal insulation and oil spill absorption.

[0015] Beneficial effects:

[0016] The modified halloysite nanotube reinforced MTES / VTMS based SiO 2 In the preparation method of aerogel, halloysite nanotubes, as a natural nano-morphological aluminosilicate material, can be mined and purified from clay minerals and have a wide source. Their unique tubular structure and a large amount of Al-OH and Si-OH on the inner and outer surfaces provide the possibility of functionalization of halloysite nanotubes. By grafting long-chain alkyl groups thereon, the methyl groups at the ends of the long-chain alkyl groups on the surface of the halloysite nanotubes rebound with the methyl groups in the aerogel skeleton. During the drying stage, this effect can offset the skeleton collapse caused by surface tension and retain the integrity of the aerogel structure to a certain extent (i.e., the aerogel sample does not break after drying, which can be observed by the naked eye or optical photographs). In addition, the tubular structure will form high-density gas voids in the polymer, breaking the continuity of the gas heat transfer path, which can effectively reduce the thermal conductivity of the composite material.

[0017] The modified halloysite nanotube reinforced MTES / VTMS based SiO 2 Aerogel has a low shrinkage rate, certain hydrophobicity and adsorption properties, good thermal stability and low thermal conductivity.

[0018] The modified halloysite nanotube reinforced MTES / VTMS based SiO 2The thermal conductivity of the composite aerogel can reach 0.04-0.06W / m·k, and the maximum adsorption efficiency is 620% of its own mass. By changing the content of halloysite nanotubes, the heat propagation path in the aerogel can be limited, and the adsorption amount of oil by the composite aerogel can also be increased.

[0019] The modified halloysite nanotube reinforced MTES / VTMS based SiO 2 Aerogel has great potential in the fields of building energy conservation, thermal insulation, and oil spill absorption. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:

[0021] Figure 1 The modified halloysite nanotube-reinforced MTES / VTMS-based SiO 2 Optical photographs of composite aerogels; among them, (a) is an optical photograph of OMVSA-9 (used to demonstrate its low-density characteristics, which can be placed on petals without bending the flowers), (b) is an optical photograph of OMVSA-0, (c) is an optical photograph of OMVSA-1, (d) is an optical photograph of OMVSA-3, (e) is an optical photograph of OMVSA-5, (f) is an optical photograph of OMVSA-7, and (g) is an optical photograph of OMVSA-9.

[0022] Figure 2 The modified halloysite nanotube-reinforced MTES / VTMS-based SiO prepared in Examples 1-5 of the present invention 2 Composite aerogel and SiO2 of Comparative Example 1 2 Thermal insulation performance test results of composite aerogel;

[0023] Figure 3 The modified halloysite nanotube-reinforced MTES / VTMS-based SiO prepared in Examples 1-5 of the present invention 2 Composite aerogel and SiO2 of Comparative Example 1 2 Composite aerogel adsorption performance test results;

[0024] Figure 4 The modified halloysite nanotube-reinforced MTES / VTMS-based SiO prepared in Examples 1-5 of the present invention 2 Composite aerogel and SiO2 of Comparative Example 1 2 The test results of the shrinkage rate of composite aerogel. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0026] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0027] The present invention aims to solve the problem of large shrinkage of current silica aerogels and provide a modified halloysite nanotube-reinforced MTES / VTMS-based SiO 2 Method for preparing aerogel.

[0028] Modified Halloysite Nanotube Enhanced MTES / VTMS-based SiO 2 The preparation method of aerogel comprises the following steps: (1) mixing halloysite nanotubes, octadecyltrimethoxysilane (ODTMS), tetraethyl orthosilicate (TEOS), anhydrous ethanol and ammonia water to carry out hydrolysis and condensation reaction to obtain a white suspension, performing solid-liquid separation on the white suspension, collecting the obtained solid, washing and drying the solid to obtain modified halloysite nanotubes; (2) fully stirring methyltriethoxysilane (MTES), vinyltrimethoxysilane (VTMS), deionized water and anhydrous ethanol, adding hydrochloric acid to adjust the pH value and hydrolyzing to obtain a precursor solution; (3) ultrasonically treating the modified halloysite nanotubes and the precursor solution to obtain a mixed solution; (4) adding ammonia water to the mixed solution to adjust the pH value, mixing evenly, standing at room temperature to obtain a wet gel, aging and drying to obtain a modified halloysite nanotube enhanced MTES / VTMS-based SiO 2 Aerogel.

[0029] The modified halloysite nanotube reinforced MTES / VTMS based SiO 2 In the preparation method of aerogel, octadecyltrimethoxysilane (ODTMS) as a modifier and tetraethyl orthosilicate (TEOS) as a coupling agent are used to modify the surface of halloysite nanotubes (TEOS can promote the grafting of long-chain alkyl groups of ODTMS with halloysite nanotubes), and long-chain alkyl groups are grafted onto the outer surface of halloysite nanotubes through a condensation reaction catalyzed by ammonia water; methyltriethoxysilane (MTES) and vinyltrimethoxysilane (VTMS) are used as co-precursors to prepare a thermal insulation material (modified halloysite nanotubes reinforced MTES / VTMS-based SiO 2Aerogel). The addition of modified halloysite nanotubes enhances the rebound effect inside the aerogel, effectively alleviating the shrinkage and cracking that are prone to occur in the aerogel during normal pressure drying. Its rich tubular structure can increase the oil absorption of the aerogel and limit the thermal convection of gas molecules, effectively reducing the thermal conductivity of the material.

[0030] The halloysite nanotubes used in the present invention are green and environmentally friendly, have a simple preparation process, and have great potential in reducing building energy consumption, heat preservation and insulation, and oil spill absorption.

[0031] The modified halloysite nanotube reinforced MTES / VTMS based SiO 2 In a preferred embodiment of the method for preparing aerogel, in step (1), the mass ratio of halloysite nanotubes to octadecyltrimethoxysilane is greater than 1, and the mass ratio of octadecyltrimethoxysilane to tetraethyl orthosilicate is 0.1-10 (for example, 0.1, 0.5, 1, 3, 5, 7, 9 or 10). If the amount of octadecyltrimethoxysilane and tetraethyl orthosilicate is too large, agglomeration is likely to occur during the modification of the halloysite nanotubes, and the halloysite nanotubes are separated from the solution, and a uniform suspension cannot be formed, making it difficult to achieve the modification of the halloysite nanotubes.

[0032] Preferably, the mass ratio of halloysite nanotubes, octadecyltrimethoxysilane and tetraethyl orthosilicate is 1:(0.09-0.9):(0.09-1) (for example, 1:0.09:0.09, 1:0.9:1, 1:0.5:0.5, 1:0.1:1, 1:0.9:0.1, 1:0.5:1, 1:0.9:0.5, 1:0.5:0.1 or 1:0.1:0.5, etc.); the mass ratio of halloysite nanotubes, anhydrous ethanol and aqueous ammonia is 1:(10-30):(5-15) (for example, 1:10:5, 1:30:5, 1:10:15, 1:30:15, 1:20:10, 1:20:5, 1:20:15, 1:10:10 or 1:30:10). Among them, if the amount of halloysite nanotubes is larger or the amount of octadecyl trimethoxysilane is too small, the modification may not be thorough; similarly, when the amount of tetraethyl orthosilicate is too small, the hydroxyl groups on the surface of the halloysite nanotubes cannot fully react with it, resulting in a reduced modification effect. When the amounts of octadecyl trimethoxysilane and tetraethyl orthosilicate are both large, the halloysite nanotubes will agglomerate on the stirring bar during the reaction and cannot form a uniform suspension; anhydrous ethanol plays the role of a cosolvent and cannot be replaced by other reagents in the present invention; if the amount of anhydrous ethanol is too large, it may further dilute the modifier in the mixed solution and slow down the rate of the hydrolysis condensation reaction; ammonia water plays the role of base catalysis and cannot be replaced by other bases in the present invention. The amount of ammonia water only affects the reaction rate of the condensation reaction; if other types of silanes are used instead of octadecyl trimethoxysilane, the hydrophobicity of the halloysite nanotubes may be affected by the length of the alkyl chain.

[0033] Preferably, the mass ratio of halloysite nanotubes, octadecyltrimethoxysilane and tetraethyl orthosilicate is 1:(0.8-1):(0.8-1) (for example, 1:0.8:0.8, 1:1:0.8, 1:0.8:0.1, 1:1:1, 1:0.9:1, 1:1:0.9, etc.); the mass ratio of halloysite nanotubes, anhydrous ethanol and aqueous ammonia is 1:(25-30):(5-10) (for example, 1:25:5, 1:30:5, 1:25:10, 1:30:10, 1:28:8, etc.).

[0034] More preferably, the mass ratio of halloysite nanotubes, octadecyltrimethoxysilane and tetraethyl orthosilicate is 1:0.9:0.9, 1:0.9:0.09, 1:0.09:0.9, 1:0.5:0.5 or 10:1:10.

[0035] The modified halloysite nanotube reinforced MTES / VTMS based SiO 2In a preferred embodiment of the method for preparing aerogel, in step (1), the temperature of the hydrolysis condensation reaction is 50-65°C (e.g., 50°C, 55°C, 60°C or 65°C), and the reaction is carried out for 1-2h (e.g., 1h, 1.5h or 2h); thereafter, the reaction is continued under stirring at room temperature for 12-24h (e.g., 12h, 15h, 18h, 21h or 24h) to obtain a white suspension. When the hydrolysis condensation temperature is higher, the reaction rate is higher; when the reaction time is longer, the reaction is more thorough.

[0036] The modified halloysite nanotube reinforced MTES / VTMS based SiO 2 In a preferred embodiment of the method for preparing aerogel, in step (1), solid-liquid separation of the white suspension is achieved by centrifugation, the centrifugal speed is 5000-10000 rpm (for example, 5000 rpm, 6000 rpm, 7000 rpm, 8000 rpm, 9000 rpm or 10000 rpm), and the centrifugal time is 5-30 min (for example, 5 min, 10 min, 15 min, 20 min, 25 min or 30 min).

[0037] The modified halloysite nanotube reinforced MTES / VTMS based SiO 2 In a preferred embodiment of the method for preparing aerogel, in step (2), the molar ratio of methyltriethoxysilane to vinyltrimethoxysilane is (0.7-1):(0.1-1) (for example, 1:0.1, 1:0.3, 1:0.5, 1:1, 0.7:1 or 1:0.7); the molar ratio of methyltriethoxysilane, anhydrous ethanol and deionized water is 1:(5-9):(10-20) (for example, 1:5:10, 1:5:20, 1:9:10, 1:9:20, 1:7:15, 1:7:10, 1:7:20, 1:5:15 or 1:9:15); in step (3), the amount of modified halloysite nanotubes is 1%-9% (for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8% or 9%) of the total mass of methyltriethoxysilane and vinyltrimethoxysilane. Wherein, in step (2), when the content of vinyltrimethoxysilane is too high (relative to methyltriethoxysilane), it may have a certain impact on the flexibility of the product of the present invention, and the product will be harder; anhydrous ethanol acts as a co-solvent, and deionized water acts as a hydrolysis.

[0038] The modified halloysite nanotube reinforced MTES / VTMS based SiO 2In a preferred embodiment of the method for preparing aerogel, in step (2), an acid (such as hydrochloric acid; other organic acids or inorganic acids may also be used) is added to adjust the pH to 4 to 7 (for example, 4, 5, 6 or 7). In step (2), the hydrolysis temperature is 25 to 60°C (for example, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C), and the hydrolysis time is 8 to 12h (for example, 8h, 9h, 10h, 11h or 12h). Among them, when the hydrolysis temperature is too low, the rate of the hydrolysis reaction will be greatly reduced, resulting in a long gel time and a fragile gel network structure.

[0039] The modified halloysite nanotube reinforced MTES / VTMS based SiO 2 In a preferred embodiment of the method for preparing aerogel, in step (3), ammonia water is added to adjust the pH to 7 to 9 (e.g., 7, 7.5, 8, 8.5 or 9). The mixing in step (3) refers to stirring first and then ultrasonic treatment, the ultrasonic frequency is 20 to 60 kHz (e.g., 20 kHz, 30 kHz, 40 kHz, 50 kHz or 60 kHz), and the ultrasonic time is 0.5 to 2 h (e.g., 0.5 h, 1 h, 1.5 h or 2 h).

[0040] The modified halloysite nanotube reinforced MTES / VTMS based SiO 2 In a preferred embodiment of the method for preparing aerogel, in step (4), the aging time is 12 to 48 h (for example, 12 h, 20 h, 30 h, 40 h or 48 h); the drying temperature is 50 to 70 ° C (for example, 50 ° C, 55 ° C, 60 ° C, 65 ° C or 70 ° C), and the drying time is 24 to 72 h (for example, 24 h, 30 h, 40 h, 50 h, 60 h or 72 h).

[0041] The present invention also proposes a modified halloysite nanotube-enhanced MTES / VTMS-based SiO 2 Aerogel, modified halloysite nanotubes reinforced MTES / VTMS-based SiO 2 The aerogel was prepared by the method described above.

[0042] The modified halloysite nanotube reinforced MTES / VTMS based SiO 2 Aerogel has a low shrinkage rate, certain hydrophobicity and adsorption properties, good thermal stability and low thermal conductivity.

[0043] The present invention also proposes the modified halloysite nanotube-enhanced MTES / VTMS-based SiO 2 Aerogel Application: Modified Halloysite Nanotubes Reinforced MTES / VTMS-based SiO 2The application of aerogel in at least one of building energy saving, thermal insulation and oil spill absorption.

[0044] The modified halloysite nanotube reinforced MTES / VTMS based SiO 2 Aerogel has great potential in the fields of building energy conservation, thermal insulation, and oil spill absorption.

[0045] The modified halloysite nanotubes reinforced MTES / VTMS based SiO 2 Aerogel and its preparation method and application are described in detail.

[0046] All raw materials used in the following examples can be purchased commercially; the sources of the main raw materials are as follows: halloysite nanotubes (HNTs) were purchased from Guangdong Jina New Materials Technology Co., Ltd.; tetraethyl orthosilicate (TEOS, 98%) was purchased from Tianjin Hongyan Chemical Reagent Factory Co., Ltd.; octadecyltrimethoxysilane (ODTMS, 97%) was purchased from Shanghai Titan Technology Co., Ltd.; methyltriethoxysilane (MTES, 98%) was purchased from Shanghai McLean Biochemical Co., Ltd.; vinyltrimethoxysilane (VTMS, 98%) was provided by Shanghai Yien Chemical Technology Co., Ltd.; ammonia (25%-28%), n-hexane (98%) and anhydrous ethanol were provided by Tianjin Kaimao Chemical Reagent Co., Ltd.; hydrochloric acid was provided by Guangdong Guangshi Chemical Reagent Factory Co., Ltd.

[0047] Example 1

[0048] The modified halloysite nanotubes of this embodiment reinforced MTES / VTMS-based SiO 2 The preparation method of aerogel comprises the following steps:

[0049] (1) Modification of halloysite nanotubes: 10 g of halloysite nanotubes were weighed and dispersed in 250 mL of anhydrous ethanol at room temperature, 9 g of octadecyltrimethoxysilane and 9 g of tetraethyl orthosilicate were added thereto, 40 mL of ammonia water was slowly poured into the mixture, and the mixture was stirred at 1200 r / min for 1.5 h in a 65°C water bath, and then stirred for 24 h at room temperature (25°C) to allow the reaction to continue; after the stirring was completed, the obtained white suspension was placed in a centrifuge tube and centrifuged at 8000 r / min for 10 min to obtain a supernatant and a lower white precipitate; the supernatant was removed, and the white precipitate was washed with anhydrous ethanol to remove the unreacted solvent; finally, the washed white precipitate was placed in a vacuum drying oven at 60°C and dried for 18 h to obtain modified halloysite nanotubes, referred to as OHNTs;

[0050] (2) First, methyltriethoxysilane, vinyltrimethoxysilane, anhydrous ethanol and deionized water were mixed in a beaker at a molar ratio of 1:0.7:6:16 at room temperature, and stirred at a speed of 1000 r / min for 1 hour. After stirring, a certain amount of hydrochloric acid was added to adjust the pH to 4, and a layer of PVC preservative film was covered on the top of the beaker, and the mixture was placed in a constant temperature drying oven at 50° C. for hydrolysis for 10 hours to obtain a precursor solution;

[0051] (3) adding 1% of the mass of OHNTs (the amount of OHNTs is 1% of the sum of the mass of methyltriethoxysilane and vinyltrimethoxysilane) to the precursor solution, and ultrasonicating at a frequency of 40 kHz for 2 h at room temperature;

[0052] (4) After ultrasound, a certain amount of ammonia water was added dropwise to the suspension to adjust the pH to 9, and after vigorous stirring for 5 min to mix evenly, the suspension was allowed to stand and wait for gelation; the wet gel was covered with anhydrous ethanol and aged for 48 h, and then placed in a drying oven at 60 ° C for several hours to obtain the modified halloysite nanotube-enhanced MTES / VTMS-based SiO 2 aerogel, denoted as OMVSA-1.

[0053] Example 2

[0054] The modified halloysite nanotubes of this embodiment reinforced MTES / VTMS-based SiO 2 The preparation method of aerogel comprises the following steps:

[0055] (1) Modification of halloysite nanotubes: 10 g of halloysite nanotubes were weighed and dispersed in 250 mL of anhydrous ethanol at room temperature, 9 g of octadecyltrimethoxysilane and 9 g of tetraethyl orthosilicate were added thereto, 40 mL of ammonia water was slowly poured into the mixture, and the mixture was stirred at 1200 r / min for 1.5 h in a 65°C water bath, and then stirred for 24 h at room temperature (25°C) to allow the reaction to continue; after the stirring was completed, the obtained white suspension was placed in a centrifuge tube and centrifuged at 8000 r / min for 10 min to obtain a supernatant and a lower white precipitate; the supernatant was removed, and the white precipitate was washed with anhydrous ethanol to remove the unreacted solvent; finally, the washed white precipitate was placed in a vacuum drying oven at 60°C and dried for 18 h to obtain modified halloysite nanotubes, referred to as OHNTs;

[0056] (2) First, methyltriethoxysilane, vinyltrimethoxysilane, anhydrous ethanol and deionized water were mixed in a beaker at a molar ratio of 1:0.7:6:16 at room temperature, and stirred at a speed of 1000 r / min for 1 hour. After stirring, a certain amount of hydrochloric acid was added to adjust the pH to 4, and a layer of PVC preservative film was covered on the top of the beaker, and the mixture was placed in a constant temperature drying oven at 50° C. for hydrolysis for 10 hours to obtain a precursor solution;

[0057] (3) adding 3% of the mass of OHNTs (the amount of OHNTs is 3% of the sum of the mass of methyltriethoxysilane and vinyltrimethoxysilane) to the precursor solution, and ultrasonicating at a frequency of 40 kHz for 2 h at room temperature;

[0058] (4) After ultrasound, a certain amount of ammonia water was added dropwise to the suspension to adjust the pH to 9, and after vigorous stirring for 5 minutes, the suspension was allowed to stand and wait for gelation; the wet gel was covered with anhydrous ethanol and aged for 48 hours, and then placed in a drying oven at 60° C. for several hours to obtain the modified halloysite nanotube-enhanced MTES / VTMS-based SiO 2 aerogel, denoted as OMVSA-3.

[0059] Example 3

[0060] The modified halloysite nanotubes of this embodiment reinforced MTES / VTMS-based SiO 2 The preparation method of aerogel comprises the following steps:

[0061] (1) Modification of halloysite nanotubes: 10 g of halloysite nanotubes were weighed and dispersed in 250 mL of anhydrous ethanol at room temperature, 9 g of octadecyltrimethoxysilane and 9 g of tetraethyl orthosilicate were added thereto, 40 mL of ammonia water was slowly poured into the mixture, and the mixture was stirred at 1200 r / min for 1.5 h in a 65°C water bath, and then stirred for 24 h at room temperature (25°C) to allow the reaction to continue; after the stirring was completed, the obtained white suspension was placed in a centrifuge tube and centrifuged at 8000 r / min for 10 min to obtain a supernatant and a lower white precipitate; the supernatant was removed, and the white precipitate was washed with anhydrous ethanol to remove the unreacted solvent; finally, the washed white precipitate was placed in a vacuum drying oven at 60°C and dried for 18 h to obtain modified halloysite nanotubes, referred to as OHNTs;

[0062] (2) First, methyltriethoxysilane, vinyltrimethoxysilane, anhydrous ethanol and deionized water were mixed in a beaker at a molar ratio of 1:0.7:6:16 at room temperature, and stirred at a speed of 1000 r / min for 1 hour. After stirring, a certain amount of hydrochloric acid was added to adjust the pH to 4, and a layer of PVC preservative film was covered on the top of the beaker, and the mixture was placed in a constant temperature drying oven at 50° C. for hydrolysis for 10 hours to obtain a precursor solution;

[0063] (3) adding 5% of the mass of OHNTs (the amount of OHNTs is 5% of the sum of the mass of methyltriethoxysilane and vinyltrimethoxysilane) to the precursor solution, and ultrasonicating at a frequency of 40 kHz for 2 h at room temperature;

[0064] (4) After ultrasound, a certain amount of ammonia water was added dropwise to the suspension to adjust the pH to 9, and after vigorous stirring for 5 minutes, the suspension was allowed to stand and wait for gelation; the wet gel was covered with anhydrous ethanol and aged for 48 hours, and then placed in a drying oven at 60° C. for several hours to obtain the modified halloysite nanotube-enhanced MTES / VTMS-based SiO 2 Aerogel, denoted as OMVSA-5.

[0065] Example 4

[0066] The modified halloysite nanotubes of this embodiment reinforced MTES / VTMS-based SiO 2 The preparation method of aerogel comprises the following steps:

[0067] (1) Modification of halloysite nanotubes: 10 g of halloysite nanotubes were weighed and dispersed in 250 mL of anhydrous ethanol at room temperature, 9 g of octadecyltrimethoxysilane and 9 g of tetraethyl orthosilicate were added thereto, 40 mL of ammonia water was slowly poured into the mixture, and the mixture was stirred at 1200 r / min for 1.5 h in a 65°C water bath, and then stirred for 24 h at room temperature (25°C) to allow the reaction to continue; after the stirring was completed, the obtained white suspension was placed in a centrifuge tube and centrifuged at 8000 r / min for 10 min to obtain a supernatant and a lower white precipitate; the supernatant was removed, and the white precipitate was washed with anhydrous ethanol to remove the unreacted solvent; finally, the washed white precipitate was placed in a vacuum drying oven at 60°C and dried for 18 h to obtain modified halloysite nanotubes, referred to as OHNTs;

[0068] (2) First, methyltriethoxysilane, vinyltrimethoxysilane, anhydrous ethanol and deionized water were mixed in a beaker at a molar ratio of 1:0.7:6:16 at room temperature, and stirred at a speed of 1000 r / min for 1 hour. After stirring, a certain amount of hydrochloric acid was added to adjust the pH to 4, and a layer of PVC preservative film was covered on the top of the beaker, and the mixture was placed in a constant temperature drying oven at 50° C. for hydrolysis for 10 hours to obtain a precursor solution;

[0069] (3) adding 7% of the mass of OHNTs (the amount of OHNTs is 7% of the sum of the mass of methyltriethoxysilane and vinyltrimethoxysilane) to the precursor solution, and ultrasonicating at a frequency of 40 kHz for 2 h at room temperature;

[0070] (4) After ultrasound, a certain amount of ammonia water was added dropwise to the suspension to adjust the pH to 9, and after vigorous stirring for 5 minutes, the suspension was allowed to stand and wait for gelation; the wet gel was covered with anhydrous ethanol and aged for 48 hours, and then placed in a drying oven at 60° C. for several hours to obtain the modified halloysite nanotube-enhanced MTES / VTMS-based SiO 2 Aerogel, denoted as OMVSA-7.

[0071] Example 5

[0072] The modified halloysite nanotubes of this embodiment reinforced MTES / VTMS-based SiO 2 The preparation method of aerogel comprises the following steps:

[0073] (1) Modification of halloysite nanotubes: 10 g of halloysite nanotubes were weighed and dispersed in 250 mL of anhydrous ethanol at room temperature, 9 g of octadecyltrimethoxysilane and 9 g of tetraethyl orthosilicate were added thereto, 40 mL of ammonia water was slowly poured into the mixture, and the mixture was stirred at 1200 r / min for 1.5 h in a 65°C water bath, and then stirred for 24 h at room temperature (25°C) to allow the reaction to continue; after the stirring was completed, the obtained white suspension was placed in a centrifuge tube and centrifuged at 8000 r / min for 10 min to obtain a supernatant and a lower white precipitate; the supernatant was removed, and the white precipitate was washed with anhydrous ethanol to remove the unreacted solvent; finally, the washed white precipitate was placed in a vacuum drying oven at 60°C and dried for 18 h to obtain modified halloysite nanotubes, referred to as OHNTs;

[0074] (2) First, methyltriethoxysilane, vinyltrimethoxysilane, anhydrous ethanol and deionized water were mixed in a beaker at a molar ratio of 1:0.7:6:16 at room temperature, and stirred at a speed of 1000 r / min for 1 hour. After stirring, a certain amount of hydrochloric acid was added to adjust the pH to 4, and a layer of PVC preservative film was covered on the top of the beaker, and the mixture was placed in a constant temperature drying oven at 50° C. for hydrolysis for 10 hours to obtain a precursor solution;

[0075] (3) adding 9% of the mass of OHNTs (the amount of OHNTs is 9% of the sum of the mass of methyltriethoxysilane and vinyltrimethoxysilane) to the precursor solution, and ultrasonicating at a frequency of 40 kHz for 2 h at room temperature;

[0076] (4) After ultrasound, a certain amount of ammonia water was added dropwise to the suspension to adjust the pH to 9, and after vigorous stirring for 5 minutes, the suspension was allowed to stand and wait for gelation; the wet gel was covered with anhydrous ethanol and aged for 48 hours, and then placed in a drying oven at 60° C. for several hours to obtain the modified halloysite nanotube-enhanced MTES / VTMS-based SiO 2 Aerogel, denoted as OMVSA-9.

[0077] Example 6

[0078] The modified halloysite nanotubes of this embodiment reinforced MTES / VTMS-based SiO 2 The preparation method of aerogel comprises the following steps:

[0079] (1) Modification of halloysite nanotubes: 10 g of halloysite nanotubes were weighed and dispersed in 250 mL of anhydrous ethanol at room temperature, 9 g of octadecyltrimethoxysilane and 9 g of tetraethyl orthosilicate were added thereto, 40 mL of ammonia water was slowly poured into the mixture, and the mixture was stirred at 1200 r / min for 1.5 h in a 65°C water bath, and then stirred for 24 h at room temperature (25°C) to allow the reaction to continue; after the stirring was completed, the obtained white suspension was placed in a centrifuge tube and centrifuged at 8000 r / min for 10 min to obtain a supernatant and a lower white precipitate; the supernatant was removed, and the white precipitate was washed with anhydrous ethanol to remove the unreacted solvent; finally, the washed white precipitate was placed in a vacuum drying oven at 60°C and dried for 18 h to obtain modified halloysite nanotubes, referred to as OHNTs;

[0080] (2) First, methyltriethoxysilane, vinyltrimethoxysilane, anhydrous ethanol and deionized water were mixed in a beaker at a molar ratio of 1:0.7:6:16 at room temperature, and stirred at a speed of 1000 r / min for 1 hour. After stirring, a certain amount of hydrochloric acid was added to adjust the pH to 4, and a layer of PVC preservative film was covered on the top of the beaker, and the mixture was placed in a constant temperature drying oven at 50° C. for hydrolysis for 8 hours to obtain a precursor solution;

[0081] (3) adding 9% of the mass of OHNTs (the amount of OHNTs is 9% of the sum of the mass of methyltriethoxysilane and vinyltrimethoxysilane) to the precursor solution, and ultrasonicating at room temperature at a frequency of 20 kHz for 2 h;

[0082] (4) After ultrasound, a certain amount of ammonia water was added dropwise to the suspension to adjust the pH to 9, and after vigorous stirring for 5 minutes, the suspension was allowed to stand and wait for gelation; the wet gel was covered with anhydrous ethanol and aged for 48 hours, and then placed in a drying oven at 60° C. for several hours to obtain the modified halloysite nanotube-enhanced MTES / VTMS-based SiO 2 aerogel, denoted as OMVSA-9a.

[0083] Example 7

[0084] The modified halloysite nanotubes of this embodiment reinforced MTES / VTMS-based SiO 2 The preparation method of aerogel comprises the following steps:

[0085] (1) Modification of halloysite nanotubes: 10 g of halloysite nanotubes were weighed and dispersed in 250 mL of anhydrous ethanol at room temperature, 9 g of octadecyltrimethoxysilane and 9 g of tetraethyl orthosilicate were added thereto, 40 mL of ammonia water was slowly poured into the mixture, and the mixture was stirred at 1200 r / min for 1.5 h in a 65°C water bath, and then stirred for 24 h at room temperature (25°C) to allow the reaction to continue; after the stirring was completed, the obtained white suspension was placed in a centrifuge tube and centrifuged at 8000 r / min for 10 min to obtain a supernatant and a lower white precipitate; the supernatant was removed, and the white precipitate was washed with anhydrous ethanol to remove the unreacted solvent; finally, the washed white precipitate was placed in a vacuum drying oven at 60°C and dried for 18 h to obtain modified halloysite nanotubes, referred to as OHNTs;

[0086] (2) First, methyltriethoxysilane, vinyltrimethoxysilane, anhydrous ethanol and deionized water were mixed in a beaker at a molar ratio of 1:0.7:6:16 at room temperature, and stirred at a speed of 1000 r / min for 1 hour. After stirring, a certain amount of hydrochloric acid was added to adjust the pH to 4, and a layer of PVC preservative film was covered on the top of the beaker, and the mixture was placed in a constant temperature drying oven at 50° C. for hydrolysis for 12 hours to obtain a precursor solution;

[0087] (3) adding 9% of the mass of OHNTs (the amount of OHNTs is 9% of the sum of the mass of methyltriethoxysilane and vinyltrimethoxysilane) to the precursor solution, and ultrasonicating at a frequency of 60 kHz for 2 h at room temperature;

[0088] (4) After ultrasound, a certain amount of ammonia water was added dropwise to the suspension to adjust the pH to 9, and after vigorous stirring for 5 minutes, the suspension was allowed to stand and wait for gelation; the wet gel was covered with anhydrous ethanol and aged for 48 hours, and then placed in a drying oven at 60° C. for several hours to obtain the modified halloysite nanotube-enhanced MTES / VTMS-based SiO 2 aerogel, denoted as OMVSA-9b.

[0089] Example 8

[0090] The modified halloysite nanotubes of this embodiment reinforced MTES / VTMS-based SiO 2 The preparation method of the aerogel is different from that of Example 1 only in that in step (1), the amount of halloysite nanotubes is 10 g, the amount of octadecyltrimethoxysilane is 5 g, and the amount of ethyl orthosilicate is 5 g; the rest is the same as that of Example 1. It is denoted as OMVSA-1a.

[0091] Example 9

[0092] The modified halloysite nanotubes of this embodiment reinforced MTES / VTMS-based SiO 2The preparation method of the aerogel is different from that of Example 1 only in that in step (1), the amount of halloysite nanotubes is 10 g, the amount of octadecyltrimethoxysilane is 1 g, and the amount of ethyl orthosilicate is 10 g; the rest is the same as that of Example 1. It is denoted as OMVSA-1b.

[0093] Example 10

[0094] The difference between this embodiment and embodiment 1 is that the mass of ethyl orthosilicate in step (1) is 0.9 g; the rest is the same as embodiment 1. It is denoted as OMVSA-1c.

[0095] Embodiment 11

[0096] The difference between this embodiment and embodiment 1 is that the mass of octadecyltrimethoxysilane in step (1) is 0.9 g; the rest is the same as embodiment 1. It is denoted as OMVSA-1d.

[0097] Example 12

[0098] The modified halloysite nanotubes of this embodiment reinforced MTES / VTMS-based SiO 2 The only difference between the preparation method of the aerogel and that of Example 3 is that in step (2), the molar ratio of methyltriethoxysilane to vinyltrimethoxysilane is 1:0.1; the rest is the same as that of Example 3. It is denoted as OMVSA-1e.

[0099] Example 13

[0100] The modified halloysite nanotubes of this embodiment reinforced MTES / VTMS-based SiO 2 The only difference between the preparation method of the aerogel and that of Example 3 is that in step (2), the molar ratio of methyltriethoxysilane to vinyltrimethoxysilane is 1:0.4; the rest is the same as that of Example 3. It is denoted as OMVSA-1f.

[0101] Embodiment 14

[0102] The difference between this embodiment and embodiment 1 is that the molar ratio of methyltriethoxysilane to vinyltrimethoxysilane in step (2) is 1:1; the rest is the same as embodiment 1. It is denoted as OMVSA-1g.

[0103] Embodiment 15

[0104] The difference between this embodiment and embodiment 1 is that the molar ratio of methyltriethoxysilane to vinyltrimethoxysilane in step (2) is 0.7:1; the rest is the same as embodiment 1. It is denoted as OMVSA-1h.

[0105] Comparative Example 1

[0106] The SiO 2 The preparation method of aerogel comprises the following steps:

[0107] (1) First, methyltriethoxysilane, vinyltrimethoxysilane, anhydrous ethanol and deionized water were mixed in a beaker at a molar ratio of 1:0.7:6:16 at room temperature, and stirred at a speed of 1000 r / min for 1 hour. After stirring, a certain amount of hydrochloric acid was added to adjust the pH to 4, and a layer of PVC preservative film was covered on the top of the beaker, and the mixture was placed in a constant temperature drying oven at 50° C. for hydrolysis for 10 hours to obtain a precursor solution;

[0108] (2) A certain amount of ammonia water was added dropwise to the precursor solution to adjust the pH to 9, and after vigorous stirring for 5 minutes, the solution was allowed to stand and wait for gelation; the wet gel was covered with anhydrous ethanol and aged for 48 hours, and then placed in a drying oven at 60° C. for several hours to obtain SiO 2 aerogel, denoted as OMVSA-0.

[0109] Comparative Example 2

[0110] The difference between this comparative example and Example 4 is that the halloysite nanotubes are not modified in this comparative example (i.e., step (1) is omitted, and an equal amount of halloysite nanotubes are used to replace the modified halloysite nanotubes in step (3)); the rest is consistent with Example 4.

[0111] Comparative Example 3

[0112] The difference between this comparative example and Example 2 is that VTMS in the silicon source is removed and only MTES is used as the silicon source (i.e., the ratio of the precursors in step (2) is 1:6:16 (methyltriethoxysilane: anhydrous ethanol: deionized water); the rest is consistent with Example 2.

[0113] Comparative Example 4

[0114] The difference between this comparative example and Example 2 is that the silicon source MTES / VTMS is replaced with TEOS (that is, step (2) uses only TEOS as the silicon source; the amount of OHNTs used is 3% of the mass of TEOS; the molar ratio of TEOS to anhydrous ethanol and deionized water in this comparative example is 1:9:3, and the performance of the product prepared at this molar ratio is relatively good); the rest is consistent with Example 2.

[0115] Comparative Example 5

[0116] The difference between this comparative example and Example 5 is that the silicon source MTES / VTMS is replaced by TEOS (i.e., only TEOS is used as the silicon source in step (2); the amount of OHNTs used is 9% of the mass of TEOS; the molar ratio of TEOS to anhydrous ethanol and deionized water in this comparative example is 1:9:3, and the performance of the product prepared at this molar ratio is relatively good); the rest is consistent with Example 5.

[0117] Comparative Example 6

[0118] The modified halloysite nanotubes reinforced MTES / VTMS based SiO 2 The only difference between the preparation method of aerogel and Example 1 is that in step (1), the amount of halloysite nanotubes used is 10 g, the amount of octadecyltrimethoxysilane used is 10 g, and the amount of tetraethyl orthosilicate used is 1 g; the rest is consistent with Example 1.

[0119] Comparative Example 7

[0120] The difference between this comparative example and Example 1 is that the octadecyltrimethoxysilane in step (1) is replaced by an equal amount of methyltriethoxysilane; the rest is consistent with Example 1.

[0121] Comparative Example 8

[0122] The difference between this comparative example and Example 1 is that the octadecyltrimethoxysilane in step (1) is replaced by an equal amount of vinyltrimethoxysilane; the rest is the same as Example 1.

[0123] Experimental example

[0124] 1. Optical photos

[0125] The modified halloysite nanotubes reinforced MTES / VTMS-based SiO2 in Examples 1-5 were photographed by camera. 2 Aerogels (OMVSA-1, OMVSA-3, OMVSA-5, OMVSA-7 and OMVSA-9) and SiO 2 Optical photos of aerogels, such as Figure 1 shown.

[0126] Figure 1 (a) and (g) show macroscopic photographs of OMVSA-9, and (b) to (f) show macroscopic photographs of OMVSA-0 (Comparative Example 1) to OMVSA-7, respectively.

[0127] from Figure 1It can be seen that the samples of all the examples have a certain degree of integrity, and the low density allows the sample (Example 5) to be placed on the petals without bending the flower; the sample of OMVSA-0 (Comparative Example 1) has cracks (see Figure 1 (b)), destroying the integrity of the sample.

[0128] 2. Modified Halloysite Nanotube Enhanced MTES / VTMS-Based SiO 2 Aerogel and comparative SiO 2 The density, shrinkage, thermal conductivity and adsorption of aerogels were tested:

[0129] Thermal conductivity: The SiO prepared in the examples and comparative examples was tested under ambient conditions using a thermal conductivity meter (TPS2500S, Sweden). 2 Thermal conductivity of aerogels;

[0130] density:

[0131]

[0132] Wherein: m represents the mass of the embodiment / comparative example, and V represents the volume of the embodiment / comparative example.

[0133] Shrinkage:

[0134] Where: d represents the sample diameter of the embodiment / comparative example before drying, d a It shows the diameter of the sample of Example / Comparative Example after drying.

[0135] Adsorption capacity:

[0136] Where: m represents the mass of the example / comparative example before oil adsorption, m a The mass of the examples / comparative examples after oil absorption is shown. The type of oil used in the adsorption test is engine oil.

[0137] The test results are shown in Table 1 and Figure 2-4 As shown:

[0138] Table 1

[0139]

[0140]

[0141] Through the analysis of the experimental examples and comparative data, it can be seen that in comparative example 6, agglomeration occurred during the modification of halloysite nanotubes, and the nanotubes and the solution were separated from each other, and the purpose of modification was not achieved, and it was not suitable for preparing composite aerogels. In comparative examples 7 and 8, a suspension with floccules was generated during the modification of halloysite nanotubes, which did not meet the requirements of the embodiment; after replacing octadecyltrimethoxysilane with methyltriethoxysilane or vinyltrimethoxysilane, a small part of gel was generated because ethyl orthosilicate underwent hydrolysis and condensation reaction with the two, and the modification effect could not be exerted.

[0142] The phenomenon in the above comparative examples (Comparative Examples 6-8) only occurs in step (1). There is no experimental or comparative significance in carrying out step (2) without achieving the effect of step (1). The final performance is not characterized, which is indicated by “ / ” in Table 1.

[0143] In terms of silicon source selection, for pure SiO 2 Aerogel, the addition of VTMS can effectively improve the shrinkage phenomenon of aerogel. And MTES / VTMS aerogel has lower shrinkage and thermal conductivity than TEOS aerogel. In terms of enhancement, the modified halloysite nanotubes are obviously beneficial to the enhancement of the adsorption capacity of MTES / VTMS aerogel. The modified halloysite nanotubes of the present invention enhance the MTES / VTMS-based SiO 2 Aerogel Silica aerogel has great application prospects in building energy conservation, thermal insulation and oil spill absorption.

[0144] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing modified halloysite nanotube-enhanced MTES / VTMS-based SiO2 aerogel, characterized in that: The steps include: (1) mixing halloysite nanotubes, octadecyltrimethoxysilane, ethyl orthosilicate, anhydrous ethanol and ammonia water for hydrolysis and condensation reaction to obtain a white suspension, performing solid-liquid separation on the white suspension, collecting the obtained solid, washing and drying the solid, and obtaining modified halloysite nanotubes; (2) fully stirring methyltriethoxysilane, vinyltrimethoxysilane, deionized water and anhydrous ethanol, adding hydrochloric acid to adjust the pH for hydrolysis, and obtaining a precursor solution; (3) mixing the modified halloysite nanotubes and a precursor solution to obtain a mixed solution; (4) adding ammonia water to the mixed solution to adjust the pH value, mixing evenly and then standing at room temperature to obtain a wet gel, aging and drying, thereby obtaining the modified halloysite nanotube-reinforced MTES / VTMS-based SiO2 aerogel.

2. The method for preparing the modified halloysite nanotube-enhanced MTES / VTMS-based SiO2 aerogel according to claim 1, characterized in that: In step (1), the mass ratio of halloysite nanotubes to octadecyltrimethoxysilane is greater than 1, and the mass ratio of octadecyltrimethoxysilane to ethyl orthosilicate is 0.1-10; The mass ratio of halloysite nanotubes, anhydrous ethanol and ammonia water is 1:(25-30):(5-10).

3. The method for preparing the modified halloysite nanotube-enhanced MTES / VTMS-based SiO2 aerogel according to claim 1, characterized in that: In step (1), the temperature of the hydrolysis condensation reaction is 50-65° C., and the reaction time is 1-2 h. Afterwards, the reaction is continued under stirring at room temperature for 12-24 h to obtain a white suspension.

4. The method for preparing the modified halloysite nanotube-enhanced MTES / VTMS-based SiO2 aerogel according to claim 1, characterized in that: In step (1), the solid-liquid separation of the white suspension is achieved by centrifugation, the centrifugal speed is 5000-7000 rpm, and the centrifugal time is 5-10 min.

5. The method for preparing the modified halloysite nanotube-enhanced MTES / VTMS-based SiO2 aerogel according to claim 1, characterized in that: In step (2), the molar ratio of methyltriethoxysilane to vinyltrimethoxysilane is (0.7-1):(0.1-1), and the molar ratio of methyltriethoxysilane, anhydrous ethanol and deionized water is 1:(5-9):(10-20); In step (3), the amount of the modified halloysite nanotubes is 1% to 9% of the total mass of the methyltriethoxysilane and vinyltrimethoxysilane.

6. The method for preparing the modified halloysite nanotube-enhanced MTES / VTMS-based SiO2 aerogel according to claim 1, characterized in that: In step (2), the acid is added to adjust the pH to pH = 4 to 7; In step (2), the hydrolysis temperature is 25 to 60° C., and the hydrolysis time is 8 to 12 hours.

7. The method for preparing the modified halloysite nanotube-reinforced MTES / VTMS-based SiO2 aerogel according to claim 1, characterized in that: In step (3), the ammonia water is added to adjust the pH to pH=7-9; The mixing in step (3) refers to stirring first and then ultrasonic treatment, the frequency of the ultrasound is 20 to 60 Hz, and the time of the ultrasound is 0.5 to 2 hours.

8. The method for preparing the modified halloysite nanotube-reinforced MTES / VTMS-based SiO2 aerogel according to claim 1, characterized in that: In step (4), the aging time is 12 to 48 hours; The drying temperature is 50-70° C., and the drying time is 24-72 hours.

9. A modified halloysite nanotube reinforced MTES / VTMS based SiO2 aerogel, characterized in that: The modified halloysite nanotube-reinforced MTES / VTMS-based SiO2 aerogel is prepared by the method described in any one of claims 1-8.

10. Use of the modified halloysite nanotube-reinforced MTES / VTMS-based SiO2 aerogel as claimed in claim 9 in at least one of building energy saving, thermal insulation and oil spill absorption.